High levels of mercury and low levels of persistent organic pollutants in a tropical seabird in French Guiana, the Magnificent frigatebird, Fregata magnificens. (July 2016) - Sebastiano, Manrico; Bustamante, Paco; Costantini, David; Eulaers, Igor; Malarvannan, Govindan; Mendez-Fernandez, Paula; Churlaud, Carine; Blévin, Pierre; Hauselmann, Antoine; Dell'Omo, Giacomo; Covaci, Adrian; Eens, Marcel; et al.
Abstract: In the present study, trace elements and persistent organic pollutants (POPs) were quantified from Magnificent frigatebirds ( Fregata magnificens ) breeding at a southern Atlantic island. Stable isotope ratio of carbon ( δ 13 C) and nitrogen ( δ 15 N) were also measured to infer the role of foraging habitat on the contamination. For another group from the same colony, GPS tracks were recorded to identify potential foraging areas where the birds may get contaminated. Fourteen trace elements were targeted as well as a total of 40 individual POPs, including organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs). The concentration of Hg in the blood was up to 6 times higher in adults (5.81 ± 1.27 μg g −1 dw.) than in nestlings (0.99 ± 0.23 μg g −1 dw.). A similar pattern was found for POPs. ∑PCBs was the prevalent group both in adults (median 673, range 336–2801 pg g −1 ww.) and nestlings (median 41, range 19–232 pg g −1 ww.), followed by the sum of dichlorodiphenyltrichloroethanes and metabolites (∑DDTs), showing a median value of 220 (range 75–2342 pg g −1 ww.) in adults and 25 (range 13–206 pg g −1 ww.) in nestlings. The isotope data suggested that the accumulation of trace elements and POPs between adults and nestlings could be due to parental foraging in two different areas during incubation and chick rearing, respectively, or due to a shift in the feeding strategies along the breeding season. In conclusion, our work showed high Hg concentration in frigatebirds compared to non-contaminated seabird populations, while other trace elements showed lower values within the expected range in other seabird species. Finally, POP exposure was found generally lower than that previously measured in other seabird species. Highlights: POPs, trace elements and isotopes were measured in frigatebirds, a marine predator. Both adults and nestlings had very high levels of mercury in the blood. POPs were generally low and trace elements were generally in the normal range. Isotopes suggested an effect of area or strategy of foraging on bird contamination. Abstract : In the present study we found high levels of mercury and low levels of persistent organic pollutants in a tropical seabird breeding in a protected area.